Rediscovery of Bauhinia conceptionis (Leguminosae: Cercidoideae), a rare and endemic species of Colombian legume from Chocó - Colombia, after eighty years - Castellanos, Cesar; Vargas, Frank (Phytotaxa, 2022)
During a series of botanical fieldtrips in the rural areas of the municipality of Quibdó in the Pacific region of Colombia, between 2017 and 2018, a very small population of Bauhinia conceptionis Britton & Killip (Leguminosae: Cercidoideae) was detected. Bauhinia conceptionis, a rare and endemic species of Colombian legume was described based on specimens collected by W. A. Archer in 1931. Since then, the species has not been recorded again. Bauhinia conceptionis is distinguished from other Colombian species of Bauhinia by the following combination of characters: leaves suborbicular and bilobed for less than 1/5 their length, leaf base cordate and apical lobe rounded, stigma oblique – capitate, bud up to 5.5 cm long, and distribution restricted to the Chocó area. The stigma, anther and fruits are described for the first time, since the original description. We report the rediscovery of this species in its natural habitat, surroundings of La Concepcion River, area municipality of Quibdó, in a disturbed area of tropical rainforest subject to strong anthropogenic pressures including illegal logging; additionally, new taxonomic information of this specie is provided.